Assessment of the Current Pollution Status of Jabi Lake in the Federal Capital Territory, Abuja, Nigeria - Cyril Kanayochukwu Ezeamaka; Sadiq Queen; Daful Mwanret; Ogbole Moses; Anjide Theresa Wado (Indonesian Journal of Geography, 2019)
This paper was aimed at providing the pollution status of Jabi Lake, FCT Abuja. 13 parameters were tested from raw water collected four sampling points. The physicochemical parameters were measured using Hanna multiparametric meter, while transparency was measured using Secchi disc. Dissolved oxygen, Biological and Chemical oxygen demand were measured titrimetrically using standard method. The concentrations of the metals were determined in triplicates. Flame atomic absorption spectrometer was used in the analysis as well as descriptive statistics (mean, standard deviation) and standard error. The Nigerian Industrial Standard and WHO guidelines for domestic water were used to compare the results of the water from the lake. The study reveals that the mean turbidity ranged between 21.6 – 24.2cm and is above the recommended limits of both WHO and NIS. The range of pH was between 6.3 and 8.8. pH is within a neutral range. The study reveals that the mean value of TDS and electrical conductivity is below the recommended limit of both WHO and NIS guidelines. The study shows that there is high concentration of some heavy metals (Cd, Cu, Ni, Mn, Zn, and Fe) in Jabi Lake. Cd, Zn, Fe and Ni are above the permissible limits of the NIS and WHO guidelines, which is an indication of pollution. The study, therefore, recommends that proactive measures be taken on environmental laws in FCT and that environmental/health worker and non-governmental bodies be active in enlightenment campaigns that will alert members of the public to the harm being caused to this important ecosystem.